Demokrasi dan Pengawas Pemilu - Dede Sri Kartini (Journal of Governance, 2017)
The Implementation of democracy is easily known as a one of theinvolvement of the people in determining their leader through the election. But theimplementation of elections without supervision is impossible to produce freeelections, confidential, honest and fair. Electoral supervision theoretically stilluse management concepts that certainly need discourse to find concepts and eventhe definition of appropriate electoral supervision. This literature study intends todiscuss the definition of electoral supervision, the scope of electoral supervision,the types of election violations, and then link it with democracy. The history ofelectoral supervision will also be presented as an opening of this paper. Tooversee democracy, it is necessary to control elections that are structurallyimplemented from the BAWASLU to the PANWASLU in the Villages, as well asparticipatory oversight by involving volunteers from the community.